Preventive Maintenance Of The Cooling System On The Main Engine On The Mt. Ratu Zainab - Nalle, Carles YA; Ashar , Ashar (Jurnal Improsci, 2025)
Background. The main drive engine is an energy conversion engine that converts thermal energy resulting from chemical reactions between fuel and air into mechanical energy. The process of burning the fuel occurs due to high air pressure in the combustion chamber. Aims. This research was conducted on the MT ship. Ratu Zainab aims to determine the best practices for preventive maintenance of the cooling system on the main engine and identify the factors that impact her work on the MT ship. Queen Zainab. Methods. The method used is qualitative descriptive. The study's results highlight the importance of regular maintenance for the freshwater cooling system to ensure optimal engine performance. The main steps include preparing maintenance schedules, creating checklists, and conducting periodic inspections. Result. Common problems that often occur include a lack of suction in the cooling pump, decreased impeller performance, dirt accumulation in the seals, and leaks in the intercooler cover, thus affecting the cooling system of the main engine on the MT. Ratu Zainab's ship. Daily and monthly maintenance is recommended to detect damage early. Factors that affect the performance of the cooling system include corrosion, clogging of the cooler by dirt, and wear and tear on the standard components. Proper preventive maintenance can reduce damage, improve operational efficiency, and extend the life of machine components. Cooling system failure can lead to overheating, reduced engine efficiency, and severe component damage. Therefore, implementing preventive maintenance is a strategic step to prevent unexpected damage. Conclusion. This research highlights the importance of proactive maintenance and a thorough understanding of seawater cooling systems to ensure the optimal and safe operation of ships. Implementation. Thus, implementing proper preventive maintenance on the main engine cooling system is a crucial effort in ensuring the safety, efficiency, and reliability of the overall ship operation.